Level of depression and hopelessness among women with infertility during the outbreak of COVID-19: a cross-sectional investigation - Banuhan Şahin; Buğra Şahin; Pervin Karlı; Görker Sel; Şafak Hatırnaz; Osman Fadıl Kara; Andrea Tinelli (IMR Press, 2021)
Background: Novel coronavirus disease 2019 (COVID-19) outbreak negatively impacted on the mental wellbeing of infertile couples, because of the World Health Organization's recommendation to stop all fertility treatments. This study aims to investigate the level of depression and hopelessness during the COVID-19 outbreak, in women with primary and secondary infertility. Methods: A 16-item online questionnaire was applied to a total of 220 women with primary and secondary infertility in June 2020. Participants' knowledge and concerns about COVID-19 pandemic stop of treatments and follow-up preferences were evaluated. In addition, the Beck Depression Inventory (BDI) and the Beck Hopelessness Scale (BHS) were adapted to Turkish and applied to each participant. Total scores of inventories between women were calculated. The correlation between depression and hopelessness levels of the groups was evaluated. Results: The BDI and BHS mean scores of 220 infertile women who completed our questionnaire were 14.63 ± 9.123 and 5.43 ± 5.026 and Cronbach's α-values were 0.853 and 0.904, respectively. It was found that 142 women with secondary infertility had higher mean depression and hopelessness scores (15.92 ± 9.758, 11.81 ± 6.501; P = 0.001) VS 78 women with primary infertility (6.51 ± 5.262, 3.78 ± 3.670; P = 0.000). A strong positive correlation was detected between depression and hopelessness levels for each group (r = 0.625, P = 0.000 and r = 0.740, P = 0.000). Conclusions: Total depression and hopelessness scores of both groups were in a strong positive correlation with primary and secondary infertility during the COVID-19 outbreak. Particularly, women with secondary infertility had mild depression and low levels of hopelessness.